Influence of rainfall and rainy day on oil palm productivity 7, 15, and 19 years aged in Aek Loba PT. Socfin Indonesia - andilaw rico doani sipahutar; - irsal; lisa mawarni (Universitas Sumatera Utara, 2019)
Rain is the main source of water in oil palm plantations and a factor that greatly affects the growth and production of crops. This research was to evaluate the effect of rainfall and rain day on the productivity of oil palm aged 7, 15 and 19 years.This research is done in Aek Loba Plantation PT.Socfin Indonesia. District Asahan Province of North Sumatera from July until october. This reasearch used primary data available in company administration. Primary data for the purposes of data analysis includes fresh fruit bunches (FFB) production in 2014, 2015, and 2016, rainfall data and rain day data monthly in 2013, 2014, and 2015. Analysis method used are double linier regression and correlation analysis. The model tested its feasibility with classical assumption test including normality test, heteroscedasticity test, multicolinearity test, and autocorrelation test using SPSS.v.22 for windows. From the classical assumption test conducted, it is concluded that the regression equation in oil palm plant age 7, 15, and 19 years has been qualified to be followed by multiple linear regression analysis and correlation analysis. The result of regression analysis shows that rainfall and rainy day variables have no significant effect on increasing the productivity of FFB in oil palm crop at age 7, 15 and 19 years at α 5 % (sig < α 0,05). The results of the analysis on plants aged 7, 15, and 19 years with two-way analysis showed significantly rainfall and rainfall variables on FFB productivity. In 7 years old oil palm trees showed enough correlation with value of 0.602 and 0.606. In 15 years old oil palm trees showed a rather week correlation of 0.544; 0.477. In 19 years old oil palm trees showed a rather week and week correlation of 0.494; 0.372.